2016
DOI: 10.1097/md.0000000000004203
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of gender for renal progression in patients with early chronic kidney disease

Abstract: Risk factors for chronic kidney disease (CKD), such as hypertension, hyperglycemia, albuminuria, renal structure, and sex hormones, have been reported to have different effects on males and females. Thus, CKD progression may differ depending on sex. In addition to CKD management, treatment at earlier stages can reduce complications and prevent disease progression as well as high medical expenses at late stages. We examined the differences in predictive risk factors for renal progression between male and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 41 publications
6
55
2
6
Order By: Relevance
“…Blood pressure elevation is one of the most effective risk factors for both development of CKD and for the progression of the disease. 3,19,20 In our study, PCPE-1 levels in the CKD patient group with uncontrolled BP were significantly higher than those in the control group. Positive correlation was determined between SBP and PCPE-1 in the patient group as a whole, but separate correlation analyses among patients with controlled and uncontrolled BP revealed no significant relation between SBP and PCPE-1.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Blood pressure elevation is one of the most effective risk factors for both development of CKD and for the progression of the disease. 3,19,20 In our study, PCPE-1 levels in the CKD patient group with uncontrolled BP were significantly higher than those in the control group. Positive correlation was determined between SBP and PCPE-1 in the patient group as a whole, but separate correlation analyses among patients with controlled and uncontrolled BP revealed no significant relation between SBP and PCPE-1.…”
Section: Discussioncontrasting
confidence: 41%
“…Blood pressure elevation is one of the most effective risk factors for both development of CKD and for the progression of the disease . In our study, PCPE‐1 levels in the CKD patient group with uncontrolled BP were significantly higher than those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, to accelerate the progression of DN, and hence to more closely mimic human pathophysiology, unilateral nephrectomy can be applied leading to additional hemodynamic stress on the remaining kidney (Bower, Brown, Steffes, Vernier, & Mauer, 1980). Despite evidence of sex-associated differences in the progression of DN in human patients (Carrero, Hecking, Chesnaye, & Jager, 2018;Chang et al, 2016;Piccoli, Alrukhaimi, Liu, Zakharova, & Levin, 2018), male mice are predominantly being used in preclinical DN research and drug development including the majority of previous studies in the UNx db/db mouse model of DN (Ninichuk, Khandoga, et al, 2007;Ninichuk, Kulkarni, Clauss, & Anders, 2007;Senador, Kanakamedala, Irigoyen, Morris, & Elased, 2009;Yiu et al, 2016). In this study, we therefore compared the progression of DN in male and female UNx db/db C57BLKS mice using standard biochemical and histological endpoints, as well as renal cortex transcriptomic changes.…”
Section: Impact Of Sex On Diabetic Nephropathy and The Renal Transcrimentioning
confidence: 99%
“…Previous studies have proposed that men show a lower risk of CKD with higher levels of vigorous intensity physical activity compared with women, while shorter sitting times are associated with CKD in women, but not in men [26]. A possible explanation for this finding is that cultural and social environmental differences and biological effects have caused sex differences [35][36][37]. It has been reported that estrogens may bring into play potent antioxidant action and may have protective effects on renal progression in women [38].…”
Section: Discussionmentioning
confidence: 99%